2015
DOI: 10.1016/j.ijimpeng.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A study of the penetration behaviour of mild-steel-cored ammunition against boron carbide ceramic armours

Abstract: The low mass and high specific strength of composite systems has led to their widespread adoption in aerospace applications. Consequently their performance under impact from offnormal events, or even deliberate insult, for example from a munition such as an anti-aircraft missile, is of paramount importance. Experimental and computational work to-date has typically focused on the response of composite systems to impact from projectiles with simple spherical or cylindrical geometries. However, such geometries ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Ballistic protective structures could be constructed using metal alloys (e.g., BR7 class steel) [4], ceramics (e.g., B 4 C) [5], and composite materials (e.g., aramid reinforced composites) [6]. In general, fiber reinforced composites withstand against the penetration of threat by dissipating its energy via different modes of failure mechanisms such as fiber fracture, fiber pull out, fiber split, fiber-matrix debonding, matrix cracking [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ballistic protective structures could be constructed using metal alloys (e.g., BR7 class steel) [4], ceramics (e.g., B 4 C) [5], and composite materials (e.g., aramid reinforced composites) [6]. In general, fiber reinforced composites withstand against the penetration of threat by dissipating its energy via different modes of failure mechanisms such as fiber fracture, fiber pull out, fiber split, fiber-matrix debonding, matrix cracking [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, a cover plate with enough thickness is still necessary to prevent it from bulging, indicating that an optimal thickness value exists for the cover plate. Many new cover materials have been developed, such as fiber-reinforced polymer (FRP) [20], glass fiber composite materials [21,22] and boron carbide composite materials [23], while their experimental results need to be further discussed. In general, metal cover plates are more commonly used at present; Zhai et al [17] confirmed that the performance of the armored steel cover plate is the best, followed by copper.…”
Section: Introductionmentioning
confidence: 99%
“…As the key component in lightweight layered armour composites, ceramic materials provide the high resistance and energy dissipation capacity against penetrating impact. The ballistic performance of such armour ceramics has been studied experimentally and numerically under a range of small calibre ammunition impact [1][2][3][4][5][6]. The design and optimisation of the armour composite system require the accurate prediction of the penetration behaviour of ceramic materials subjected to high speed impact loading.…”
Section: Introductionmentioning
confidence: 99%